Letters written to András Hegedűs (Hegedűs Andráshoz írott levelek)
In this series there are also letters from the period when he was still an active politician, among them some of extreme importance, such as those written by Rákosi and Gerő. However, the great majority consists of letters written to him in the later period of his life. The letters he received after his memoirs were published contain supplementary comments, or propose corrections or modifications to the texts. The letters inviting him to various conferences are also filed into this series. In Hungarian: Ebbe a sorozatba soroltuk a Hegedűs politikusi periódusából származó, kiemelkedő fontosságú leveleket (Rákositól, Gerőtől, stb). Lényegesen nagyobb hányadot jelentenek a későbbi időszakban neki küldött levelek. Külön kategóriát képeznek azok a levelek, melyeket a visszaemlékezéseit tartalmazó könyveiről írtak neki kiegészítésként, módosító javaslatként, vagy gratulációként. A különböző előadásokra történt felkéréseket, konferencia-meghívásokat is ez a sorozat tartalmazza. A legtöbb levelet megírásuk dátuma szerint csoportosítottuk. Accruals not expected